Caracterização agronômica e morfológica de populações de milho - Silva, Tallyta Nayara [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The efficiency of selection can be broadened for certain trait using estimates of genetic parameters, that allow to identify the nature of the action of the genes involved in the control of the traits and evaluate the efficiency of different breeding strategies to obtain genetic gains. Path analysis is one of the methods to estimate the correlation, a genetic parameter, and provides a detailed understanding of the influences of the traits involved in a diagram previously established, justifying the existence of positive and negative correlations, high and low magnitudes among the traits studied. Thus, this study aimed to verify the variability and correlation between agronomic and morphology traits in synthetic maize populations, in order to practice indirect selection. The 13 synthetic populations of maize were evaluated at field experiments in Jaboticabal-SP and Campo Alegre de Goiás-GO in regular season crop (2009/2010) and off-season crop (2010), using a randomized block design. The traits considered were lodging, culm breakage, plant height, ear height and grain yield. The 13 populations were also sown in 1 kg-plastic bags under black shade cloth, using a randomized complete block design with nine replications. Evaluation of the following morphological traits was performed: root fresh matter, root dry matter, main root length, average root diameter, root surface area, root tissue density and shoots dry matter. The trait grain yield exhibited great genetic variability, indicating to be effective if used for selection. The selection on the morphological traits is more indicated on root dry matter, due to the ease in obtaining data and its accuracy, high correlation with all morphological traits and association with grain yield. The simultaneous selection based on the traits root fresh matter and root dry matter, for gains in grain yield, can be performed. The highest direct effect on grain ...

A eficiência de seleção pode ser ampliada para determinado caráter utilizando-se estimativas de parâmetros genéticos, que permitem identificar a natureza da ação dos genes envolvidos no controle dos caracteres e avaliar a eficiência de diferentes estratégias de melhoramento para a obtenção de ganhos genéticos. A análise de trilha é um dos métodos de se estimar a correlação, um parâmetro genético, e proporciona um conhecimento detalhado das influências dos caracteres envolvidos em um diagrama previamente estabelecido, justificando a existência de correlações positivas e negativas, de altas e baixas magnitudes entre os caracteres estudados. Assim, objetivou-se verificar a existência de variabilidade e correlação entre caracteres agronômicos e morfológicos em populações sintéticas de milho, visando seleção indireta. Foram utilizadas 13 populações sintéticas de milho, avaliadas em experimentos de campo em Jaboticabal-SP e Campo Alegre de Goiás-GO na safra de 2009/2010 e safrinha de 2010, utilizando-se o delineamento em blocos casualizados. Os caracteres considerados foram acamamento, quebramento, altura de plantas, altura de espiga, e produtividade de grãos. As 13 populações também foram semeadas em sacos plásticos de 1 kg sob sombrite, utilizando-se delineamento em blocos casualizados com nove repetições. Foi realizada avaliação das características morfológicas: matéria fresca de raiz, matéria seca de raiz, comprimento da raiz principal, diâmetro médio de raiz, área de superfície da raiz, densidade de tecido radicular e matéria seca da parte aérea. O caráter produtividade de grãos apresentou grande variabilidade genética, indicando ser eficiente se utilizado para seleção. A seleção sobre os caracteres morfológicos é mais indicada sobre matéria seca de raiz, devido à facilidade e precisão na obtenção dos dados, alta correlação ...
Keywords: Milho; Seleção de plantas - Melhoramento genetico; Genetica vegetal; Plantas - Melhoramento genetico; Produtividade agrícola; Plant-breeding